How Tax Insights and Eco-Perceptions Shape Electric Vehicle Purchase Intentions - Rizky Dwi Prasetio; Hommy Dorthy Ellyany Sinaga (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2024)
This study aims to analyze the influence of tax tariff understanding and perception of eco-friendly products (green products) on the intention to purchase electric vehicles in Medan City, with a sample consisting of Auto2000 Medan Pancing customers. Electric vehicles are considered a potential solution to reduce greenhouse gas emissions and air pollution from conventional motor vehicles. However, the low adoption rate of electric vehicles in Medan indicates challenges in consumer interest factors. This research employed a survey method with 70 respondents from Auto2000 Medan Pancing customers, analyzed using multiple linear regression tests. The results show that both tax tariff understanding and perception of eco-friendly products, both simultaneously and partially, do not significantly affect the intention to purchase electric vehicles. These findings indicate the need for more effective policies and further consumer education on the benefits and advantages of electric vehicles.